0720 ASSOCIATION OF INDIVIDUAL PERIODIC LIMB MOVEMENTS AND NON-SUSTAINED TACHYCARDIA DURING SLEEP: A CASE-CROSSOVER ANALYSIS. (28th April 2017) - May, AM; May, RD; Bena, J; Wang, L; Monahan, K; Stone, KL; Cawthon, PM; Barrett-Connor, E; Koo, BB; Winkelman, JW; Redline, S; Mittleman, MA; et al.
Abstract: Introduction: Periodic limb movements during sleep (PLMS) and arousals are associated with sympathetic nervous system activation. We hypothesize a temporal relationship of individual PLMS, particularly those with arousal, and non-sustained ventricular tachycardia (NSVT) events. Methods: A bidirectional case-crossover design (characterized by inherently perfect subject characteristic matching) was used to assess temporal PLMS and NSVT associations in 41 Osteoporotic Fractures in Men Sleep Study participants with in-home polysomnography-identified NSVT events during sleep. Arrhythmias were annotated blinded to other data. Sleep time was divided into 30-minute segments. A priori, for each NSVT event (n=96), we selected a preceding 30-second hazard period and three randomly-chosen 30-second control periods from sleep at 5-minute intervals from the NSVT within the same 30-minute segment and evaluated for PLMS, respiratory events, and arousals. Odds ratios and 95% confidence intervals - OR(95%CI) - were determined by conditional logistic regression; covariates included arousals and respiratory events in the same hazard/control period. Interactions of PLMS and both respiratory event and arousal were examined. Results: Male participants were 79.8 ± 6.0 years with a PLMS index of 40.6(IQR:21.6, 67.1) and apnea-hypopnea index of 17.1(IQR:8.6, 26.1). PLMS were not significantly associated with NSVT (OR=1.49, 95%CI 0.70–3.17). PLMS with arousal were associated with NSVT in unadjusted analyses (OR=3.31, 95%CI 1.32–8.30) and after respiratory event adjustment (OR=3.36, 95%CI 1.34–8.46). Arousals were associated with NSVT in unadjusted analyses (OR=2.15, 95%CI 1.22–3.79), but not after PLMS-related arousals were excluded (OR=1.60, 95%CI 0.83–3.07). There were no significant interactions of PLMS and respiratory events or arousals (p=0.69 and p=0.13, respectively). Analysis of one NSVT event per participant yielded similar results. Conclusion: PLMS with (but not without) arousals are associated with >3-fold higher odds of subsequent NSVT episodes. These findings suggest PLMS-related arousals are physiologically important ventricular arrhythmia triggers. Investigation targeting PLMS with arousals to reduce ventricular arrhythmogenesis is needed. Support (If Any): The Osteoporotic Fractures in Men (MrOS) Study is supported by National Institutes of Health funding. The following institutes provide support: the National Institute on Aging (NIA), the National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS), the National Center for Advancing Translational Sciences (NCATS), and NIH Roadmap for Medical Research under the following grant numbers: U01 AG027810, U01 AG042124, U01 AG042139, U01 AG042140, U01 AG042143, U01 AG042145, U01 AG042168, U01 AR066160, and UL1 TR000128. The National Heart, Lung, and Blood Institute (NHLBI) provides funding for the MrOS Sleep ancillary study "Outcomes of Sleep Disorders in Older Men" under the following grant numbers: R01 HL071194, R01 HL070848, R01 HL070847, R01 HL070842, R01 HL070841, R01 HL070837, R01 HL070838, R01 HL070839, and R21HL108226.